Proton-Coupled Electron-Transfer Mechanism for the Radical Scavenging Activity of Cardiovascular Drug Dipyridamole - Barzegar, Abolfazl (PLOS ONE, 2012)
Dipyridamole (DIP) is a well-known pharmaceutical drug used as a coronary vasodilator and anti-platelet agent in clinics for treating several cardiovascular diseases. Primarily, the therapeutic effects of the drug are attributed to its antioxidant potency. In this research, we aim to declare the unknown antioxidant mechanism of DIP as well as its potent chain-breaking antioxidant activity in polar aqueous medium inside the cells, using different experimental methods and theoretical quantum calculations. Data demonstrated the higher antioxidant capacity of DIP against ROS and free radicals in polar cell's interior. DIP is capable of generating long living and noninvasive DIP• radicals in oxidant condition that leads to an effective “chain-breaking antioxidant” activity. Quantum computational data indicated that DIP antioxidant has more favorable ionization potential than trolox which means DIP has higher antioxidant activity. Also, data showed that the direct hydrogen-transfer is not a favorable process to construct DIP• because of high barrier energy, though electron-transfer process can more easily to produce DIP•+ with the lowest barrier energy. Altogether, the electron donating potency of DIP to reduce ferric ion, having the low anodic oxidation peak potential, producing long lived stable DIP• radicals and protecting myoblast cells from oxidation, proposed the excellent “chain-breaking antioxidant” potency via electron-transfer mechanism of this vasodilator DIP drug in polar aqueous medium.